On the taxonomy of the genera Planovalvata Dubatolov & Kishida, Stigmatophora Staudinger and Pseudomiltochrista Dubatolov & Bucsek, with description of one new species (Lepidoptera, Erebidae, Arctiinae, Lithosiini) - Volynkin, Anton V.; Dubatolov, Vladimir V.; Kishida, Yasunori (Zootaxa, 2018)
The type species of the genus Planovalvata Dubatolov & Kishida, 2012, previously incorrectly identified as Eugoa roseivena Hampson, 1894, is described as new: Planovalvata confusa Volynkin, Dubatolov & Kishida, sp. nov. Taxonomic placement of the genera Planovalvata and Pseudomiltochrista Dubatolov & Bucsek, 2016 is clarified. The combination is revised: Stigmatophora roseivena (Hampson, 1894), comb. rev. Pseudomiltochrista is synonymized with Stigmatophora and downgraded to a subgenus level. One new combination is established: Stigmatophora (Pseudomiltochrista) zolotuhini (Dubatolov & Bucsek, 2016), comb. nov. Male and female genitalia of S. roseivena are illustrated and described for the first time.